2016
DOI: 10.17795/jjhs-36469
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Beliefs and Practices of Nurses and Nursing Students for Hand Hygiene

Abstract: Background: The current study aimed to determine the knowledge, beliefs, and practices of nurses and nursing students for hand hygiene. Materials and Methods: The study population consisted of 340 subjects (164 nurses and 176 nursing students). Data collection tools included the hand hygiene belief scale and the hand hygiene practices inventory (HHPI). Chi-square and independent samples Ttests were used for data analysis. Results: The mean scores of the HHPI were 66.36 ± 7.08 and 64.52 ± 4.90 for nurses and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
(45 reference statements)
2
9
0
3
Order By: Relevance
“…In one study the mean hand hygiene scores among student nurses were found to be 34.26/40, 86.39/115 and 64.52/70 for knowledge, belief, and practice respectively. 14 This study also has shown that the mean hand hygiene scores among dental students were 5.90, 7.21 and 5.39 out of 10 for knowledge, belief, and practice respectively. In one study among dental students the average knowledge score was 4.2 out of 10 while the attitude and practice scores were represented by 10.2 out of 12 and 5.4 out of 6, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…In one study the mean hand hygiene scores among student nurses were found to be 34.26/40, 86.39/115 and 64.52/70 for knowledge, belief, and practice respectively. 14 This study also has shown that the mean hand hygiene scores among dental students were 5.90, 7.21 and 5.39 out of 10 for knowledge, belief, and practice respectively. In one study among dental students the average knowledge score was 4.2 out of 10 while the attitude and practice scores were represented by 10.2 out of 12 and 5.4 out of 6, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…), Hand Hygiene Belief Scale (HHBS; Karadag et al. ), Hand Hygiene Practices Inventory (HHPI; Karadag et al. ), Hand Hygiene Knowledge (HHK; Kim et al.…”
Section: Methodsologymentioning
confidence: 99%
“…), Hand Hygiene Practices Inventory (HHPI; Karadag et al. ), Hand Hygiene Knowledge (HHK; Kim et al. ), Hand Hygiene Knowledge Inventory (HHKI; Jeong & Kim ), Hand Hygiene Questionnaire (HHQ; van de Mortel et al.…”
Section: Methodsologymentioning
confidence: 99%
“…Assessing the factors affecting hand hygiene compliance in nursing students also provide a chance to address any gaps in knowledge and practices before the students complete their course and enter into the medical community. 6,9 Under the light of above facts, the current questionnaire based study was planned and undertaken in order to assess knowledge, attitude and practices of staff nurses and nursing students regarding hand hygiene at a tertiary care teaching hospital of Central India.…”
Section: Introductionmentioning
confidence: 99%